Electromyographic and kinematic trunk analysis during the straight punch - Izumi, S.; Kaneoka, K.; Miyamoto, T.; Okubo, Y.; Hiura, M.; Miyakawa, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The contribution of the trunk muscles to spinal stability is well established. However, there is little investigative research about trunk investigating the trunk muscles in sport. The aim of this study was to analyze the electromyographic activity of trunk muscles and the three-dimensional kinematics of the trunk between skilled and novice boxers in the straight punch of the dominant hand. Methods The participants who volunteered for this study were fifteen university age males with no history of chronic low back pain. The participants were ranked as experienced (N = 8) or novice (N = 7). We used a surface electromyographic (SEMG) system and a three-dimensional motion analysis system. The straight punch was divided into 3 phases: a primary phase, a throw phase and a return phase. SEMG was used to measure activity in the superficial lumbar multifidus, transverse fibers of internal oblique, external oblique and rectus abdominis. The average-rectifird-value (ARV) electromyographic amplitude for each phase was calculated and normalized to the highest ARV amplitude from a straight punch, which attempted to elicit maximal voluntary isometric contractions (MVIC) for each muscle. The three-dimensional motion analysis was performed calculate the horizontal angle of acromion, anterior superior iliac spine (ASIS) and greater trochanter, respectively. The value which subtracted the angle of ASIS from the angle of acromion and the angle of greater trochanter from the angle of acromion were computed as an acromion / ASIS twist angle and an acromion / greater trochanter twist angle, respectively. Results In SEMG, the activity of the non-dominant transverse fibers of internal oblique was significantly greater in the novice boxer than in the experienced boxer at primary phase (experienced: 29% and novice: 130% MVIC). And the activity of the dominant transverse fibers of internal oblique was significantly greater in the novice boxer than in the experienced boxer at throw phase (experienced: 85% and novice: 173% MVIC). In the three-dimensional motion analysis, the results of investigation show differences between experienced and novice boxers in terms of the horizontal angle of greater trochanter and anterior superior iliac spine. An acromion / greater trochanter twist angle in the novice boxers was larger (p<0.1). Discussion Since the straight punch of the novice boxer was unfamiliar the transverse fibers of internal oblique in the novice boxers might be larger than in the experienced boxers. The experienced boxers rotated the whole trunk and had struck the straight punch. On the other hand, the novice boxers had struck the punch with twisting of the upper body. References Urquhart DM, Hodges PW. (2005). Eur Spine J, 14(4), 393-400.